The Urgency of Indonesian Omnibus Law Implementation Related to Foreign Investment - Laksmi Dewi, Anak Agung Sagung; Rahayu, Mella Ismelina Farma; Ujianti, Ni Made Puspasutari; Saripan, Hartini; Wibisana, Anak Agung Ngurah Adhi (Susbtantive Justice International Journal of Law, 2023)
Investment is one of the driving means of strengthening the country's economy. One of the expected ways to increase investment is through foreign investment. Various regulatory measures have been carried out by evaluating and analyzing regulations and policies related to the licensing process for foreign investment. A new legal breakthrough is in the form of the enactment of the Omnibus Law on the Job Creation Law that is being pursued by the government aims to make it easier for foreign investors to obtain a permit. The formulation of problems that can be studied include how the omnibus law applies to simplifying licensing in an effort to facilitate the licensing process related to foreign investment. This study aims to examine the urgency of the implementation the Omnibus Law to simplify the licensing process in an effort to facilitate foreign investment in Indonesia. This research is a normative legal research, which uses primary, secondary, and tertiary legal materials. The results of the study show that efforts to simplify the licensing process for foreign investment in Indonesia become a reference for the government with foreign investors in facilitating sustainable development efforts in the tourism sector which aims to increase large amounts of investment, the availability of jobs, and is expected to improve the country's economy. So in the application of the Omnibus Law, it is expected to be able to accommodate interests that aim to prosper the community.